Reading David Hume's 'Of the Standard of Taste' - Babich, Babette (De Gruyter, 2019)
This collection on the Standard of Taste offers a much needed resource for students and scholars of philosophical aesthetics, political reflection, value and judgments, economics, and art. The authors include experts in the philosophy of art, aesthetics, history of philosophy as well as the history of science. This much needed volume on David Hume will enrich scholars across all levels of university study and research.